An evaluation of performance of a double-leg circle on a pommel horse, and a desirable perfomance proposal - Nawa, M.; Nishiwaki, K.; Yamawaki, K.; Ikegami, Y.; Nakamura, Y.; Murai, A.; Ayusawa, K.; Yamasaki, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
For the evaluation of the performance of a double-leg circle on a pommel horse, we focused on the relation between the horizontal rotation of a body about the vertical axis in the center of a pommel horse and the hip rotation about the longitudinal axis of a body. Several gymnasts having different levels of skill were examined by using a motion capture system. The analysis shows that the horizontal rotation and the hip rotation are in good synchronization for the performance of a well-trained gymnast.